A SEMANTIC-PRAGMATIC ANALYSIS OF THE TERM "HADITH MURSAL": A STUDY OF THE BOOK AL-NUKAT ʻALĀ KITĀB IBN AL-ṢALĀḤ BY IBN HAJAR AL-ʻASQALĀNI - Andaluzi, Fahmi; Alfaen, Roby; Faikoh, Miatul; Husein, Aditya Maulana; Subandi, Fathul Alwan; Hasanah, Hasanah (Jurnal Studi Hadis Nusantara, 2024)
Along with the development of science, the discussion related to a scientific term is getting deeper. Based on the differences among scholars regarding the term mursal, this study aims to explore the term in the discourse of hadith science by focusing on Ibn Hajar al-ʻAsqalāniy's book al-Nukat ʻalā Kitāb Ibn al-Ṣalāḥ, a hadith scholar who expressed a different and more in-depth opinion regarding the term mursal. Using semantic-pragmatic analysis and based on literature review by focusing on that book as a main reference, the research results: First, the term mursal according to some scholars is attributed to the narration of the senior tabi'in only. Second, the majority of Muḥaddisīn do not differentiate between the senior and the younger Tabi'in like the first opinion. Third, the ushūlī opinion of mursal is more general, they define it as a narration whose sanad is broken in one of the ṭabaqahs whether the ṭabaqah of the tabi'in or other. Fourth, the term mursal is defined as a someone’s narration other than shahabat which is attributed to the Prophet Saw. In this regard, Ibn Hajar is in the second opinion with the majority of Muḥaddisīn who limit the term mursal to the tabi'in. By note, that this does not mean that the tabi'in narration attributed to the Prophet SAW is called a mursal, because in certain cases the narration is considered muttasil.